Kesetaraan Gender dalam Tafsir An-Nur Karya Hasbi Ash-Shiddieqy (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
In this modern era, various movements have emerged that fight for gender rights or gender equality. Islam, as a religion that brings grace to the whole of nature, does not distinguish between men and women in its teachings. In Alqauran there are 10 verses that discuss gender equality, however, some verses of the Qur'an seem discriminatory against women so they need the right interpretation to understand the true meaning. This study aims to review gender equality by referring to Tafsir An-Nur by Hasbi ash-Shiddieqy. Tafsir An-Nur is written using the ijmali method, which aims to explain the Qur'an in a language that is easy to understand by various circles. Hasbi ash-Shiddieqy interprets the Qur'an systematically, verse by verse and surah by letter, in the order of the mushaf, so that the letters and verses are interconnected. This research includes a type of qualitative research that is library research that uses thematic methods of figures with the primary source of interpretation of the Qur'anulmajid An-Nur and the secondary is books, journals, scientific works related to the teema discussed. The results of the study show that the creation of human beings was born from a married couple and Eve was not created from Adam's ribs, in the prophetic right all the messengers sent by Allah are men, in the case of marriage the guardian is allowed to refuse to marry if the prospective husband is not sekufu or if the dowry given is less than the mitsil dowry, in the leadership of the family the man has the degree of leader and the wife takes care of the household, in the public role, women only leave the house when there is an urgent need.